The impact of the World Wide Web on public relations agencies in Singapore. - Wong, Voal Voal. (2009)
The Internet, a new communication medium that has captured world-wide attention for the past few years, continues to grow strongly into the new millennium. In 1996, there were about 50 million Internet users and this figure is forecast to grow to 100 million people by the year 1999. In this light, the question of impact of the Internet becomes an important one. This project seeks to examine the impact of the World Wide Web (WWW) on public relations (PR) agencies in Singapore. The researchers explore the potential of the WWW as a PR tool, the history of the Internet and its likely developments in the near future to better understand the impact of this new medium. Through primary and secondary research data, this study argues that the WWW, as a multimedia component of the Internet, has huge potential for PR agencies as a new PR tool and that it has impact on PR agencies. The researchers conclude that WWW’s impact is symbiotic in nature, in that PR agencies might have impact the direction of this new medium.